Penggunaan Teknologi Tepat Guna untuk Pengelolaan Sampah pada Paguyuban Margo Rukun Bantul: Pengabdian - Yuli Pratiwi; Muhammad Sholeh; Joko Waluyo (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The issue of waste management in the Special Region of Yogyakarta has become increasingly complex following the closure of the Piyungan Final Disposal Site (TPA) in early 2024. One of the impacts is the increased burden of waste management at the community level. The Margo Rukun Association in Bantul is a self-reliant community that actively manages waste independently. The existing issues include limited resources and the lack of appropriate technology (TTG) in waste management. This community service activity aims to implement TTG to enhance the effectiveness of waste processing production processes, such as organic waste shredders, plastic press machines, and digital-based production management systems. The implementation methods include socialization, TTG application, and TTG usage training. The expected outcomes include significant improvements in waste management, particularly for recyclable waste. This initiative can positively impact community self-reliance and promote circular economy practices at the local level.